Modern Information Technologies in Chemical Education: Research, Analyses and Prospects for Chemistry Teachers Training [In Bulgarian] - M. Kirova (University of Sofia, 2012)
The present review paper describes the present state-of-art of two areas of the contemporary science education - the use of interactive media in teaching and learning chemistry in secondary schools and the competences of chemistry teachers for application of electronic education in these schools. A review of the current literature in those topics is presented in some details. The own contributions of the author in these areas are emphasized.